2017
DOI: 10.12659/msm.902348
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Prealbumin with Angiographic Severity in Patients with Acute Coronary Syndrome

Abstract: BackgroundSerum prealbumin (PA), which is a nutritional index, has been found to be associated with severities and prognoses of various diseases. However, there are no reports about the relationship between PA and angiographic severity of coronary artery disease.Material/MethodsThis cross-sectional study included 867 patients with acute coronary syndrome (ACS) who underwent coronary angiography. Patients were divided into quartiles of PA and coronary artery stenosis was determined by angiographic Gensini score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…12 Liver damage and inflammatory stimulation alter prealbumin levels. 13,15 Several studies of HCC and other types of cancer have suggested that prealbumin may be related to liver function and therefore show prognostic value. Nutritional status closely correlates with postoperative recurrence and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Liver damage and inflammatory stimulation alter prealbumin levels. 13,15 Several studies of HCC and other types of cancer have suggested that prealbumin may be related to liver function and therefore show prognostic value. Nutritional status closely correlates with postoperative recurrence and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with studies of cohorts in China and other countries. 13,15 Several studies of HCC and other types of cancer have suggested that prealbumin may be related to liver function and therefore show prognostic value. One study of patients with HCC found that prealbumin <140 mg/L suggests a dangerously low liver function for patients undergoing hepatectomy, 16 with prealbumin level varying directly with the extent of liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased levels of PAB could increase free thyroxine, which was associated with adverse outcomes in patients with acute myocardial infarction 31 . Clinical studies have revealed that a lower level of serum PAB was associated with prognosis of heart failure 1113 , higher overall mortality in critically ill patients 32 , and negatively associated with angiographic severity in patients with ACS 14 . The above research results illustrated that patients with low PAB levels have poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have shown that PAB in both the acute and chronic heart failure patients could predict mortality 1113 . A recent study demonstrated that the PAB level is inversely related to angiographic severity score in ACS patients 14 . In our previous study, we found that PAB could independently predict MACE in patients with ACS 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study also showed that the albumin level was not an independent risk factor for small CAA, but the PA level was an independent risk factor. A possible reason for this result is that PA has a short average lifespan; therefore, it can better estimate the nutritional and inflammatory status of a child at the precise time at which it is measured (35).…”
Section: Discussionmentioning
confidence: 99%